1994
DOI: 10.1093/carcin/15.5.889
|View full text |Cite
|
Sign up to set email alerts
|

Mutations induced by aromatic amine DNA adducts in pBR322

Abstract: A 276 bp region from the tetracycline resistance gene of the plasmid pBR322 was modified with 2-acetylaminofluorene (AAF), 2-aminofluorene (AF), 4-aminobiphenyl (ABP), N'-acetylbenzidine or 1-aminopyrene (AP) in order to determine the effect of adduct structure upon mutation induction. Each modification reaction gave one major adduct and these adducts had chromatographic properties, as determined by 32P-postlabeling, identical to those in which substitution had occurred at C8 of deoxyguanosine through the amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 0 publications
5
67
0
Order By: Relevance
“…In addition, 4-ABP is weakly but significantly mutagenic in the kidney and liver of carcinogen-treated mice. Of significance, the spectrum of mutations produced in the bladder of 4-ABP-treated mice perfectly reflects the known mutagenic potentials of 4-ABP-DNA adducts (38,42,43,(48)(49)(50). Altogether, our findings support the etiologic involvement of 4-ABP in the genesis of bladder cancer and provide a perspective on how DNA adduction leading to mutagenesis, which is specifically targeted to bladder urothelial cells, may account for bladder-tumorigenicity of this carcinogen.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, 4-ABP is weakly but significantly mutagenic in the kidney and liver of carcinogen-treated mice. Of significance, the spectrum of mutations produced in the bladder of 4-ABP-treated mice perfectly reflects the known mutagenic potentials of 4-ABP-DNA adducts (38,42,43,(48)(49)(50). Altogether, our findings support the etiologic involvement of 4-ABP in the genesis of bladder cancer and provide a perspective on how DNA adduction leading to mutagenesis, which is specifically targeted to bladder urothelial cells, may account for bladder-tumorigenicity of this carcinogen.…”
Section: Discussionsupporting
confidence: 68%
“…The "syn" conformation places the O6 and N7 atoms of the modified guanine in a position to mispair with N6 and N1 atoms of an adenine or with N1 and N2 atoms of a guanine in the complementary strand, thus, resulting in G!T or G!C transversion mutations, respectively (46,47). In vitro and/or in vivo studies in various model systems have shown that 4-ABP or its metabolites induce both G:C!T:A and G:C!C:G transversion mutations, with the former being the most prominent type of mutation (38,42,43,(48)(49)(50). Furthermore, mutation analysis of the TP53 gene in human bladder tumors has shown that G:C!A:T transition mutations are the prevalent type of mutation found in the general population or specifically in individuals with known history of exposure to aromatic amines (43).…”
Section: Discussionmentioning
confidence: 99%
“…51 The major DNA adduct was identified as N-(deoxyguanosin-8-yl)-4-ABP, 20 which has been shown to result in G:CfiT:A mutation. 50 Furthermore, in B6C3F 1 mice, 85% of 4-ABP-induced tumors had G:CfiT:A mutation in H-ras codon 61. 43 Our sequencing data also suggest that clonal expansion does not play a crucial role for the MF induced by 4-ABP in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
“…GC?TA mutations are also the predominant ones observed in studies of mutagenesis by N 2 -deoxyguanosine adducts of 1,3-butadiene (Carmical et al, 2000), adducts of 4-aminobiphenyl (Melchior et al, 1994), and 8-oxodeoxyguanosine (Moriya, 1993). Other studies of butadiene mutagenesis demonstrate the occurrence of GC?AT, AT?TA, and GC?TA mutations (Recio et al, 2000).…”
Section: Likely Mutationsmentioning
confidence: 99%